2022
DOI: 10.1021/acssuschemeng.1c08676
|View full text |Cite
|
Sign up to set email alerts
|

High Quantum Yield Boron and Nitrogen Codoped Carbon Quantum Dots with Red/Purple Emissions for Ratiometric Fluorescent IO4 Sensing and Cell Imaging

Abstract: A facile and cost-effective hydrothermal method was developed for the preparation of boron and nitrogen codoped carbon quantum dots (B,N-CQDs) from 3-carboxyphenylboronic acid and o-phenylenediamine. The synthesized B,N-CQDs exhibit excellent properties such as excellent water solubility, strong fluorescence, good dispersion, and desirable stability. The average particle size of B,N-CQDs is 2.82 nm, and the absolute fluorescence quantum yield is 86.58%. The excitation wavelength of B,N-CQDs is 300 nm. Emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…17,55 Some groups have recently reported producing highly efficient CDs, with QY ranging from ∼70–90%. 56–58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,55 Some groups have recently reported producing highly efficient CDs, with QY ranging from ∼70–90%. 56–58…”
Section: Resultsmentioning
confidence: 99%
“…17,55 Some groups have recently reported producing highly efficient CDs, with QY ranging from ∼70-90%. [56][57][58] The pH of hydroponic solutions affects the availability of certain nutrients. A lower pH (e.g., 5.5) will keep most nutrients in solution while a higher pH (e.g., >6.5) is likely to cause nutrient deprivation.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…To ensure the change in lifetime of the CQDs, lifetime study of both CQDs and CQDs+H2O were performed and it was come spectroscopic results confirmed that the quenching process is dynamic one. [70][71][72][73] FRET Process: It is a phenomenon that occurs between the excited state of the CQDs and the ground state of the quencher which may be organic molecules or inorganic analytes. [74] This phenomenon is applied in huge scale in different fields to detect various organic molecules, biologically important molecules, pesticides or inorganic metal ions which may be very important in sense of toxicity.…”
Section: Static Quenchingmentioning
confidence: 99%
“…[18][19][20][21] With their distinguished properties and abundant surface functional groups, CDs have also become exemplary optical sensors for environmental water contaminants. [22][23][24] For instance, Meng et al developed boron-doped CDs via a one-step hydrothermal method, which were used for highly selective and ultrasensitive detection of Hg 2+ via a fluorescence quenching effect, and the B-CDs also exhibited satisfactory recovery in actual water samples. 25 Liu et al reported blue fluorescent nitrogen-doped CDs, which were fabricated using anhydrous citric acids and polyethyleneimine as precursors.…”
Section: Introductionmentioning
confidence: 99%